A case series on successful pregnancy outcomes in patients with Apla syndrome - Gaur, Priyanka; Kochar, Swati; Sharma, Vaibhav (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
The antiphospholipid antibody syndrome (APS) is defined by the persistent presence of antiphospholipid antibodies in patients with recurrent venous or arterial thromboembolism or pregnancy morbidity. Obstetric complications such as recurrent pregnancy loss, oligohydramnios, preterm delivery, fetal growth restriction, preeclampsia, HELLP syndrome and fetal distress are frequently associated with antiphospholipid syndrome. Successful management of pregnancies with APLA syndrome is a huge challenge for treating obstetrician. Obstetric care is based on combined medical and obstetric high risk management and treatment with the association between aspirin and heparin. Here, we present 3 cases of pregnancy with APLA syndrome who were successfully managed and they had uneventful pregnancies with successful outcomes without any complication.